1996
DOI: 10.3382/ps.0751428
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Infusion of Adrenocorticotropin Elevates Circulating Lipoprotein Cholesterol and Corticosterone Concentrations in Chickens ,

Abstract: The purpose of the present study was to investigate the effects of elevated corticosterone (CORT) on circulating lipoprotein cholesterol during a 1-wk period. For this study, 15 commercial broilers were randomly assigned to one of three treatment groups. Group 1 served as the control (CON) and received no treatment, whereas Groups 2 and 3 received subcutaneous mini-osmotic pumps containing either physiological saline (PS) or adrenocorticotropin (ACTH), respectively. The ACTH was delivered at a rate of 8 IU/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 23 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…A dramatic affect in these younger birds was a highly signifi-cant increase (P < 0.0001) in serum triglyceride levels. The increase in triglyceride levels seen in stressed birds in the present study supports the observations seen in stress models using adrenocorticotropic hormone infusion (Latour et al, 1996;Puvadolpirod and Thaxton, 2000) and in turkeys undergoing the stressors of crowding and overheating (Kowalski et al, 2002). In the present study, the increase appears to have been modulated by YE supplementation, which significantly decreased triglyceride levels, particularly at the 500 g/ton level.…”
Section: Discussionsupporting
confidence: 92%
“…A dramatic affect in these younger birds was a highly signifi-cant increase (P < 0.0001) in serum triglyceride levels. The increase in triglyceride levels seen in stressed birds in the present study supports the observations seen in stress models using adrenocorticotropic hormone infusion (Latour et al, 1996;Puvadolpirod and Thaxton, 2000) and in turkeys undergoing the stressors of crowding and overheating (Kowalski et al, 2002). In the present study, the increase appears to have been modulated by YE supplementation, which significantly decreased triglyceride levels, particularly at the 500 g/ton level.…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that classical music can reverse the growth inhibition caused by increased stocking density and improve broiler growth performance. When birds experience stress, their HPA axis is activated, and the pituitary gland is stimulated to secrete ACTH and glucocorticoids synthesized by adrenal cortical cells (29). Puvadolpirod et al (30) found that the injection of high doses of exogenous ACTH increased corticosterone levels in the blood of broilers and increased stress levels by establishing a physiological stress model.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of models of physiological stress in chickens using the treatment with ACTH or corticosterone showed that the metabolic changes associated with stress in chicken are increased plasma glucose, total proteins, triacylglyceroles and cholesterol (Davison et al 1983;Latour et al 1996;Puvadolpirod and Thaxton 2000 ab). Response in these metabolic parameters to chronic food restriction differ in several respects.…”
Section: Discussionmentioning
confidence: 99%